The perspectives of “mild hybrid” technology for creation of vehicle hybridization system - Mykhalevych, Mykola; Shuklinov, Serhii; Dvadnenko, Volodymyr; Yaryta, Oleksandr; Михалевич, Микола Григорович; Шуклінов, Сергій Миколайович; Двадненко, Володимир Якович; Ярита, Олександр Олександрович (Харківський національний автомобільно-дорожній університет, 2022)
Problem. At the present stage of science and technology development the problem of creating energy efficient vehicles is solved by electric vehicle designing: electromobiles and hybrid vehicles. Despite perspectives of a battery electric vehicles, it could be complied with a “Zero Emissions” criterions only in case if the electricity is generated from renewable sources. In addition, electric vehicle may not always provide the desired range on charge. Lithium-ion batteries are now used to power the electric drive, and an important problem of that is a significant weight which vehicle have to carry, it is also necessary to balance their elements, which significantly increases the charging time from the external mains. Goal. The goal of the work is to develop the theoretical basis for the creation of a system for the conversion of the "mild hybrid" vehicles in operation. Methodology. Many countries cannot afford to make the rapid transition to renewable electricity and replace the fleet with electric vehicles. Instead, a faster effect can be obtained if you re-equip vehicles that are already in use to hybrids. To successfully fulfill this goal, it is necessary to justify the parameters of the hybridization system of vehicles in order to obtain significant energy efficiency with a favorable payback period. Results. The analysis of hybrid classification and drive architecture allowed to offer new functions for "micro hybrid" and "mild hybrid" technologies. Analysis of power losses during the movement of the vehicle allowed to predict the number and power of electric motors sufficient to perform new functions. Originality. The structural scheme of the hybridization system of the motor vehicle which provides its conversion into a hybrid is developed. The study is aimed primarily at improving the "mild hybrid" technology in which electric motors of relatively low power, which are not inherent in this technology, are proposed to partially implement the functions inherent in the technology of "full hybrid". Practical value. The combination of the features of "micro hybrid" and "full hybrid" technologies in "mild hybrid" technology should provide sufficient energy efficiency, ease of installation of the system equipment and low costs.
Перспективи технології “mild hybrid” для створення системи гібридизації автотранспортних засобів
Keywords: vehicle; mild hybrid; maintenance of constant movement; rational modes of movement; electric drive with frequency control; energy efficiency; автотранспортний засіб; підтримка сталого руху; раціональні режими руху; електропривод з частотним керуванням; енергоефективність; 629.01; 10.30977/AT.2019-8342.2022.50.0.04